OXYGEN CONSUMPTION OF ROCK BREAM Oplegnathus fasciatus IN DIFFERENT SALINITY LEVELS AND TEMPERATURE DEGREES [Konsumsi oksigen Ikan Rock Bream Oplegnathus fasciatus pada tingkat salinitas dan suhu yang berbeda] - Vitas Atmadi Prakoso; Jun Hyung Ryu; Byung Hwa Min; Rudhy Gustiano; Young Jin Chang (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Rock bream Oplegnathus fasciatus is one of marine fish species with high commercial value in the region of East Asia. However, studies on the metabolism related to environmental factors for this species is still lacking. This study was therefore aimed to assess the effects of salinity and temperature on oxygen consumption (OC) of rock bream (TL: 26.9±0.6 cm, BW: 477.3±61.9 g) was observed by using respiratory chamber to understand the optimal salinity and temperature for culture of rock bream. Research was conducted in Pukyong National University, Busan, South Korea. Four experimental groups were conducted to measure oxygen consumption (OC) according to salinity (35, 25, 15, and 35?5 psu) and temperature changes (15?20?25oC). The results showed that low salinity exposures tend to decrease OC of rock bream (87.1, 78.3, 66.3, and 58.5 mg O2/kg/h at 35, 25, 15, and 5 psu, respectively). Meanwhile, the oxygen consumption of rock bream increased with increasing water temperatures (35 psu: 64.7, 104.0, and 175.9 mg O2/kg/h at 15, 20, and 25oC, respectively; 25 psu: 45.8, 101.7, and 185.9 mg O2/kg/h at 15, 20, and 25oC, respectively; 15 psu: 29.8, 103.3, and 155.5 mg O2/kg/h at 15, 20, and 25oC, respectively).